Parameter estimation of Box-Jenkins model using genetic algorithm - Nur'afifah Rusdi, 1990-; Zuhaimy Ismail, supervisor; Fakulti Sains (2013)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2013